Airfoil control surface discontinuous nonlinearity experimental assessment and numerical model validation - Vasconcellos, Rui M.G. [UNESP]; Abdelkefi, Abdessattar; Hajj, Muhammad R.; Almeida, Daniel P.; Marques, Flávio D. (SAGE Publications, 2016)
A variety of dynamic behaviors that may be encountered in aeroelastic systems with discontinuous nonlinearities has motivated investigations that may support future applications in flight controls design, flutter prediction, instability characterization and energy harvesting. In this paper, the case of an airfoil with control surface freeplay is assessed experimentally and modeled numerically using an alternative continuous approximation for the discontinuous nonlinearity based on hyperbolic tangent function representation. The unsteady aerodynamic loads are computed using the modified unsteady Theodorsen approximation for arbitrary motions. The validity of the proposed freeplay representation is performed through comparison with experimental data. Adjustments to the pitching restoring moments have been carried out to account for a smooth polynomial concentrated nonlinearity. Data analysis is performed to characterize and investigate the experimental signals. Sub-critical bifurcation behavior is observed from both experimental data and the numerical model prediction. The results confirm the validity of hyperbolic tangent function combinations for freeplay nonlinearity representation for the experimental setup conditions.
Keywords: bifurcation; Experimental aeroelasticity; freeplay; nonlinear dynamics; time series analysis